The Performance Of A Newly Designed Concrete Armour Unit For Rubble Mound Breakwaters - Abdulameer, Mohammed Zuhear (2010)
Erosion and inundation, resulting from wave impacts, are challenges synonymous with the near sea location. These challenges have grown in intensity and event due to the well known phenomenon of Global Warming. Therefore, the need for stronger and more stable structures has increased. The intention of this study is to develop a new artificial armour unit used for armouring offshore rubble mound breakwaters. A design of the intended armour has been given in this study. A number of calculations for determining the layer coefficients were conducted, hence, obtaining the layer’s porosity and packing density. These characteristics were compared to other well known artificial armour units. In order to test the newly designed artificial armour unit for its hydraulic performance a number of tests were conducted. These tests are two dimensional tests that include hydraulic stability, overtopping and run-up. These tests were conducted in a hydraulic flume of a 10 m length, 0.3 m width and 0.45m height. The tests were conducted on three armour layers a rock armour layer, an armour layer composed of randomly placed newly designed armour units and the third is an armour layer made up of uniformly placed newly designed armour units. The results of the three armour layers are compared and analyzed. In conclusion, the armour unit that was presented in this study showed higher hydraulic performance than the rock armour unit. Also, the presented armour unit is more porous than some well known armour units and more economical.